Antimicrobial Stewardship in Outpatient Settings: A Systematic Review. (22nd December 2014) - Drekonja, Dimitri M.; Filice, Gregory A.; Greer, Nancy; Olson, Andrew; MacDonald, Roderick; Rutks, Indulis; Wilt, Timothy J.
Abstract : Objective: Evaluate the effect of outpatient antimicrobial stewardship programs on prescribing, patient, microbial outcomes, and costs. Design: Systematic review Methods: Search of MEDLINE (2000 through November 2013), Cochrane Library, and reference lists of relevant studies. We included English language studies with patient populations relevant to the United States (eg, infectious conditions, prescription services) evaluating stewardship programs in outpatient settings and reporting outcomes of interest. Data regarding study characteristics and outcomes were extracted and organized by intervention type. Results: We identified 50 studies eligible for inclusion, with most (29 of 50; 58%) reporting on respiratory tract infections, followed by multiple/unspecified infections (17 of 50; 34%). We found medium-strength evidence that stewardship programs incorporating communication skills training and laboratory testing are associated with reductions in antimicrobial use, and low-strength evidence that other stewardship interventions are associated with improved prescribing. Patient-centered outcomes, which were infrequently reported, were not adversely affected. Medication costs were generally lower with stewardship interventions, but overall program costs were rarely reported. No studies reported microbial outcomes, and data regarding outpatient settings other than primary care clinics are limited. Conclusions: Low- to moderate-strength evidence suggests that antimicrobial stewardship programs in outpatient settings improve antimicrobial prescribing without adversely effecting patient outcomes. Effectiveness depends on program type. Most studies were not designed to measure patient or resistance outcomes. Data regarding sustainability and scalability of interventions are limited. Infect Control Hosp Epidemiol 2014;00(0):1–11